KRISTIANITAS DI ANTARA TEGANGAN TRADISI DAN RELEVANSI - Samosir, Leonardus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2006)
The article discusses the identity of Christianity in Indonesia. The discrepancy between tradition and relevancy occurs when 'identity' is understood as static.Onthe contrary, when identity is viewed as dynamic, a dialectical balance between tradition and relevancy is required. Identity does not necessarily mean uniformity. It may instead mean 'united diversity'. The Church in Indonesia becomes 'Indonesian Church' only if she is capable of making significant interaction between the universal Church (tradition) and Indonesian peculiar situation (relevancy).